Glioblastoma and malignant melanoma: Serendipitous or anticipated association?. Issue 1 (25th October 2020) - Yang, Kevin; Stein, Thor D.; Huber, Bertrand R.; Sartor, Emmett A.; Rachlin, Jacob R.; Mahalingam, Meera
Abstract : We describe a patient who had primary glioblastoma (GB) and malignant melanoma (MM). A 78‐year‐old man presented with several weeks to months of history of gait disturbance, confusion, memory disturbance, and worsening speech. Imaging studies performed on admission revealed a large frontotemporal lobe mass associated with the surrounding zone of vasogenic edema. Given the patient's medical history of incomplete biopsy of a midback tumor performed three weeks before, the presumptive clinical diagnosis was metastatic MM. Pathological examination of frozen sections of fragmented specimens obtained at stereotactic biopsy performed on admission revealed a high‐grade malignant neoplasm characterized by discohesive cells in a blue myxoid background and abundant foci of tumor necrosis. Given these features, in conjunction with the abovementioned pathological report, the frozen section diagnosis by the neuropathologist was "neoplasm identified, favor melanoma." Due to the paucity of lesional tissue, a limited immunohistochemistry performed on the permanent sections revealed positive staining of lesional cells for Sox10 alone using a multiplex MART1/Sox10 immunostain and S‐100 protein, an immunohistochemical profile supporting the presumptive frozen section diagnosis. A tumor debulk procedure, performed two weeks later, revealed histopathologic features most compatible with GB, IDH wild‐type. Thus, additional immunohistochemistry on the permanent sections revealed positive staining of glial fibrillary acidic protein (GFAP), Sox10, and S‐100 protein as well as negative staining of gp100, a complex carbohydrate matrix protein in embryonic melanosomes, using a specific antibody HMB45. The concomitant occurrence of MM and GB in our patient underscores the association between these two entities. Our literature review suggests that the sporadic co‐occurrence of these two conditions is likely not serendipitous.